Lignin for Bioeconomy: The Present and Future Role of Technical Lignin - Ekielski, Adam; Mishra, Pawan Kumar (International journal of molecular sciences, 2020)
Lignin, the term commonly used in literature, represents a group of heterogeneous aromatic compounds of plant origin. Protolignin or lignin in the cell wall is entirely different from the commercially available technical lignin due to changes during the delignification process. In this paper, we assess the status of lignin valorization in terms of commercial products. We start with existing knowledge of the lignin/protolignin structure in its native form and move to the technical lignin from various sources. Special attention is given to the patents and lignin-based commercial products. We observed that the technical lignin-based commercial products utilize coarse properties of the technical lignin in marketed formulations. Additionally, the general principles of polymers chemistry and self-assembly are difficult to apply in lignin-based nanotechnology, and lignin-centric investigations must be carried out. The alternate upcoming approach is to develop lignin-centric or lignin first bio-refineries for high-value applications; however, that brings its own technological challenges. The assessment of the gap between lab-scale applications and lignin-based commercial products delineates the challenges lignin nanoparticles-based technologies must meet to be a commercially viable alternative.
Keywords: Plants; algoritmy; lignin; Economics; Hydrolysis; bioeconomy; Lignin; lignin nanoparticles; Biotechnology; biotechnologie; Models, Theoretical; self-assembly; ekonomika; Algorithms; teoretické modely; technical lignin; rostliny; hydrolýza